A secreted splice variant of the Xenopus frizzled-4 receptor is a biphasic modulator of Wnt signalling - Gorny, Anne-Kathrin; Kaufmann, Lilian; Swain, Rajeeb Kumar; Steinbeisser, Herbert (Cell communication and signaling, 2013)
Activation of the Wnt signalling cascade is primarily based on the interplay between Wnt ligands, their receptors and extracellular modulators. One prominent family of extracellular modulators is represented by the SFRP (secreted Frizzled-related protein) family. These proteins have significant similarity to the extracellular domain of Frizzled receptors, suggesting that they bind Wnt ligands and inhibit signalling. The SFRP-type protein Fz4-v1, a splice variant of the Frizzled-4 receptor found in humans and Xenopus, was shown to augment Wnt/β-catenin signalling, and also interacts with those Wnt ligands that act on β-catenin-independent Wnt pathways.